PENGARUH KUALITAS PRODUK, DESAIN PRODUK DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN MEBEL PADA COLLECTION FURNITURE DI PONDOK BAMBU - Ridwan, Muhammad; Desi, Sintia (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
The purpose of this study is to determine the effect of product quality, product design and price on furniture purchase decisions on Collection Furniture in Pondok Bambu. The sampling technique used is Purposive Samples. The sample in this study amounted to 96 respondents. Methods of data collection using questionnaires distributed to consumers of furniture buyers Collection Furniture in Pondok Bambu and analytical techniques used are multiple linear regression. The results show that 1). Product quality is the highest variable in influencing purchasing decisions Furniture on Collection Furnture in Pondok Bambu with products with durable texture. 2). Design becomes the second variable that influences purchasing decisions Furniture On Collection Furniture in Pondok Bambu, shows that elegant models in product design can influence consumers to buy back. 3). Price is the lowest variable affecting purchasing decisions of Furniture on Collection Furniture di Pondok Bambu.